2016
DOI: 10.1186/s13011-016-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between housing subsidies and supportive housing on neighborhood distress and housing satisfaction: does drug use make a difference?

Abstract: BackgroundSince the 1970s, the dominant model for U.S. federal housing policy has shifted from unit-based programs to tenant-based vouchers and certificates. Because housing vouchers allow recipients to move to apartments and neighborhoods of their choice, such programs were designed to improve the ability of poor families to move into neighborhoods with less concentrated poverty. However, little research has examined whether housing voucher recipients live in less distressed neighborhoods than those without h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Additionally, studies used R statistical Package, R-INLA, Geo-Mapping Software (GMS), WebGIS, and STATA for both statistical and spatial analysis. These studies used the aforementioned geospatial analysis software and tools for data visualization and mapping 11,21-23 , distribution of homeless center 24-26 or visualize results 19 related to the health-related problems and homelessness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, studies used R statistical Package, R-INLA, Geo-Mapping Software (GMS), WebGIS, and STATA for both statistical and spatial analysis. These studies used the aforementioned geospatial analysis software and tools for data visualization and mapping 11,21-23 , distribution of homeless center 24-26 or visualize results 19 related to the health-related problems and homelessness.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies included in this review reported using data from official federal or governmental data source such as the Centers for Disease Control and Prevention (CDC) in the USA; Regional Public Health Department of Montreal in Canada; Office for National Statistics and Health and Social Care Information Centre (HSCIC) in the UK; Institute for Clinical Evaluative Sciences, Canada; All-Payer Claims Databases; Statewide Planning and Research Cooperative System (SPARCS); New York State Department of Health; London Tuberculosis Register; Westminster City Council; Department for Work and Pensions (DWP), UK; Department for Education (DoE), UK. Very few studies used primary survey data 4,11,21,28,31,32 , focus group discussion data 19 , key informant interview data 24 for the health-related studies of the homeless.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States has a long and ugly history of residential segregation and we must be certain that this is not being duplicated in supportive housing programs. Previous research has suggested that Housing Choice vouchers were associated with moving to improved neighborhoods for White but not Black recipients (Pendall, 2000), and Black residents of Permanent Supportive Housing Programs were also more likely to live in distressed neighborhoods (Dickson‐Gomez, McAuliffe, Obidoa, Quinn, & Weeks, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Whether supportive housing sites are located in relatively better or worse neighborhoods than Moving On housing is also an open question. In a study of neighborhood distress, low-income residents who received housing subsidies or supportive housing were no more or less likely to live in neighborhoods with high levels of economic distress, as measured by the American Community Survey (ACS) metrics on neighborhood employment, income, education, assistance/benefits, household characteristics, and housing vacancy, than other low-income residents (Dickson-Gomez et al, 2016). In another study, recipients of project-based vouchers, a common source of affordable housing assistance utilized by PSH programs that are tied to the PSH program, were found to reside in better neighborhoods than recipients of tenant-based vouchers, a common source of affordable housing assistance utilized by MOIs that are tied to and move with the individual, despite a general lack of between-group differences in predisposing and need characteristics (Chinchilla et al, 2019).…”
Section: Introductionmentioning
confidence: 99%